Differential effect of university entrance score on first-year students' academic performance in Portugal. Issue 4 (19th May 2019) - Ferrão, Maria; Almeida, Leandro
Abstract: The main goal of this study is to show that the association between university entrance score and first-year students' academic performance varies randomly across courses after controlling for students' sociodemographic, schooling trajectory and motivational variables. The sample consists of 2697 first-year students who were enrolled in 54 courses at a Portuguese public university in 2015/16. Multilevel modelling of academic performance suggests that 34% of variability in grade point average is due to differences among courses and that 80% of such variability is explained by the field of study, whether the university is the student's first choice, and the student's gender, age and parents' level of education. In addition, the results corroborate that the university entrance score is the strongest predictor of first-year academic performance.